The Challenges Encountered by The EFL Teachers in Online Synchronous Learning at SMK Nasional Makassar - Setiawati, Nurul Sri; Sunra, La; Sakkir, Geminastiti (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aims to explore the strategies used by the teachers as well as the challenges they face in implementing the teaching and learning activities during online classes. This research is qualitative research with a case study approach through interviews. The participants in this study were 2 English teachers from SMK Nasional Makassar. The data in this study were obtained through 3 parts of interviews with a total of ten questions. The findings show that the strategies used by English teachers in implementing learning during online classes are diagnostic assessment and discovery learning using several applications, including WhatsApp, Zoom, Google Classroom, YouTube, Google Forms, and the Google search engine. The teachers also used several other strategies involving peer tutoring, using school facilities, implementing synchronous online learning, and parental counselling to overcome challenges. Meanwhile, their challenges are lack of access to technology, parental support, social influence, and student interest. Therefore, it is recommended for teachers to continue to use or apply a combination of strategies that they have implemented. In addition, because there are several other strategies discussed in this study, readers, especially teachers, can also use other strategies and technologies to increase the variety of their learning activities. Finally, during the observation of the application of discovery learning, the teacher used it to recount text materials with a combination of writing and speaking projects. It can be used differently in different material focuses and skills. So, it is also suggested that future researchers be more specific with certain aspects of teaching English, such as language skills or certain materials to enrich data related to that field.